A pyrene-fused N-heteroacene with eleven rectilinearly annulated aromatic rings - Kohl, Bernd; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2015)
A highly soluble pyrene-fused undecacene is realized by end-capping the rectilinear aromatic π-plane with triptycenylene units. Besides the good solubility, the compound shows a high tendency to crystallize. Two polymorphs from dichlorobenzene and chloroform are described. In the polymorph from chloroform, half of the molecules are strongly bent out of the π-plane by 26.4°.